Against Enforced Disappearance : The Political Detainees' Case Before the Nepal Supreme Court - Uprety, K. (2012)
Enforced disappearances, for political reasons, are still a common practice in many countries. In many instances, courts have taken bold steps to deter State agencies from orchestrating and encouraging such acts through orders and decisions. In that vein, Nepal's Supreme Court, in 2007, breaking the long tradition of a conservative and passive approach to justice, issued a verdict of significant proportion which could have a long-lasting effect on the country's political governance, both from the municipal as well as international law perspectives.